Correction to: Proposal of a new nomenclature for introns in protein-coding genes in fungal mitogenomes - Shu Zhang; Yong-Jie Zhang (IMA Fungus)
After publication of our article (Zhang and Zhang 2019) we have been notified us that the nad4L sequence should be corrected in Additional file 1. All sequences in the file should be that of NC_036382 (GenBank accession number), but have been erroneously pasted as the nad4L sequence of NC_001715.